Resistensi dan Solidaritas: Pengaruh Solidaritas dalam Mendorong Pergerakan Sosial selama Pandemi COVID-19 - Anggi Nicolin; Angga Ihza Putra Indrijanto; Krishnamurti Martin Ksatriani; Vinna Damayanti (Universitas Airlangga, 2021)
The outbreak of Coronavirus Disease 2019 (COVID-19) has swept everybody inthe international system off their feet. With high chances of contractibility andsoaring number of cases then urges every government to take action and imposenew policies to minimize the spread of the virus and to suppress the damagesthat the virus may bring. The world then take steps into a limbo period withevery economic activities stopped for great measures, accordingly governmentsand people started to feel the blow from the crisis. The realization that a globalhealth crisis need to be taken care of globally, prompts the society to take responsibilitiesand stand in solidarity to resolve the crisis. Globalization—and it’sinnovations—succeeded in forming a new pattern of identity in society. Each individualand each communities started to intertwine into one single network andone single identity as a global society, then started to carry out their mission tocreate social movements and take solidarity actions to support global collectiveaction in response to the COVID-19 pandemic.